(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
The emergence of the concept of welfare state has influenced gradual development of the role of the government for protecting the interests of consumer’s. In Indian scenario the impact of British rule has been to transform from duty conscious society to the right conscious society. Since Independence we have adopted the concept of welfare state under new constitution this has called for great intervention of state protecting the rights and interests of consumers as against strict adherence to caveat emptor principle. In the end of the nineteenth century, in the modern commercial age, the advancement in the commercial transaction, standard form of contract, globalisation brought an era of consumerism where consumers started facing exploitation by strong business class. In order to maintain social harmony legal intervention was called. By the end of nineteenth century the Anglo American jurists had summarised the whole jurisprudence upon the basis of rights of contract duty base. Gradually the emphasis was shifted from individual interests to social interest. The emergence of the concept of welfare state has influenced gradual development of the role of the government for protecting the interests of consumer’s. In the Indian scenario the impact of British rule has been to transform from duty conscious society to the right conscious society. Since Independence we have adopted the concept of welfare state under new constitution this has called for great intervention of state protecting the rights and interests of consumers as against strict adherence to caveat emptor principle. Need for protecting the interests of consumers also felt in our country. Several laws for consumer’s protection were there since 1947, but enactment of consumer’s protection Act, 1986, and new Amendment in 2002 gave more protection to consumers. The enactment of Competition Act, 2002 by replacing of MRTP Act, 1969 brought new dimensions to protection of consumer’s interests in India.